Evaluation of Refractory Autoimmune Hemolytic Anemia Patients After Splenectomy - Günhan Tekin, Mehmet; Atay, Memiş Hilmi (Cerrahpaşa Medical Journal, 2024)
Objective: In this study, we aimed to retrospectively evaluate the results of patients with autoimmune hemolytic anemia (AIHA) who had undergone splenectomy. Methods: The records of 25 patients with AIHA refractory to steroids and who underwent splenectomy between January 1, 2000, and October 31, 2017, and were followed up at Ondokuz Mayıs University were retrospectively reviewed. Patient demographics, AIHA type and secondary causes, direct Coombs subtypes, hemoglobin and lactate dehydrogenase levels at diagnosis and at postsplenectomy, bone marrow biopsy and splenectomy pathologies, liver and spleen size, splenectomy complications, treatments given presplenectomy, status after splenectomy, and relapse treatments were examined. Results: Twelve of 25 patients (48%) had primary AIHA and 13 (52%) had secondary AIHA. All patients received methylprednisolone before splenectomy. After splenectomy, 14 (56%) of the cases were in remission, while 11 (44%) relapsed. Of the patients who relapsed, steroids were used in 54.54%, rituximab in 18.18%, cyclosporine in 36.36%, intravenous immunoglobulin in 9.09%, and mycophenolate mofetil in 9.09%. One patient underwent plasmapheresis. At the end of all treatments, 6 (54.54%) patients who relapsed after splenectomy were in remission, while 3 (27.27%) relapsed and 2 (18.18%) were refractory. Four patients died. As a complication of splenectomy, sepsis developed in 4 patients (16%) and thrombotic events occured in 6 patients (24%). Conclusion: Some of the patients with AIHA did not respond to splenectomy. We think that the number of patients who need to undergo splenectomy will decrease with randomized trials using new generation drugs. Cite this article as: Tekin MG, Atay MH. Evaluation of refractory autoimmune hemolytic anemia patients after splenectomy. Cerrahpaşa Med J. 2024;48(2):135-140.